Safecrossing: pedestrian crossing assistant app for visually impaired - Lok, Jun Leong (2022)
This proposal is a project of a mobile assistant app for visually impaired people. Visually impaired peoples have risk when crossing road and they are no pedestrian around to assist them. In addition, most of the traffic light in Malaysia is didn’t install pedestrian signal system and for those installed is lack of maintenance. Hence this project is aims to develop an application to assists visually impaired to cross the road with safe condition. Since currently most of the people own their smartphone included visually impaired people, hence this project will fully implement in smartphone. Object detection is one of the functions will included in this project, it uses for recognize the surrounding object to assists the user cross the road. Besides, implement media as the output of application. By the experiment finding, TensorFlow is the suitable open source for create machine learning on object detection. In conclusion, this project will be using TensorFlow to train detection custom model and implement in mobile application to assist visually impaired crossing road.